PENGARUH METODE RESIPROKAL TERHADAP HASIL BELAJAR TENDANGAN DEPAN PENCAK SILAT - Fitriandi, Fitriandi; Purnomo, Edi; Triansyah, Andika (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2020)
the ability of the basic technique of the front kick through the reciprocal method in students of class X MIPA II students of SMAN 7 Pontianak. The purpose of this study was to determine the effect of reciprocal methods on learning outcomes of front kicks at SMAN7 Pontianak.This study uses an experimental method in the form of one group pre-test and post-test disign. In this study the number of samples amounted to 36 students in Pontianak 7 Public High Schools. Data collection in this study used a test instrument that is the Front Kick Skill Test. Data analysis using the T-test.Based on the results of data analysis, t-test 5.6 and t-table 2.14 can be obtained so that t-test> greater than T-table with this Ho is rejected and Ha is accepted, it means that there is a reciprocal method effect on the front kick learning outcomes martial arts. With the percentage of influence of 39.64%.Keywords: reciprocal, learning outcomes, pencak silat front kick.